PENERAPAN ARTIFICIAL INTELLIGENCE (AI) DALAM PERAMALAN AKUNTANSI TINJAUAN LITERATUR DAN AGENDA PENELITIAN MASA DEPAN - Pratama, Gilang Surya; Agus Munandar (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2025)
This research examines recent developments in the application of Artificial Intelligence (AI) for accounting forecasting through a systematic review of literature published between 2020-2024. Using a systematic review methodology, this study analyzed 60 selected articles from Scopus, Web of Science, Science Direct and Google Scholar databases. The analysis results show significant improvements in forecasting accuracy using AI technology, with Machine Learning achieving 78% accuracy in revenue forecasting, Deep Learning 85% in financial trend prediction, and Natural Language Processing 89% in sentiment analysis. Major implementation challenges include data quality, infrastructure limitations, and data security. Development opportunities are identified in blockchain integration, hybrid models, and preprocessing automation. This research also identifies future research agendas that include the development of adaptive models and improved AI interpretability. The contribution of this research lies in providing a comprehensive understanding of the state-of-the-art application of AI in accounting forecasting and identifying future development directions.